Production of biodiesel and analysis of exhaust particulate emissions and metal concentration of lubricant oil of the compression ignition engine - Bhangwar, Sajjad; Liaquat, Ali Memon; Luhar, Muhammad Ramzan; Abbasi, Aijaz; Kumar, Laveet; Rajput, Umair Ahmed; Mastoi, Sanaullah (Frontiers in Energy Research, 2022)
In this research Biodiesel fuel is created using a potassium hydroxide (KOH) catalyst transesterification process and using methanol as a co-solvent and dry washing it to purify the methyl ester generated. This process resulted in the production of a biodiesel rate of 93%. All biodiesel characteristics were confirmed to be within American Society for Testing and Materials (ASTM) norms. Analysis of particulate matter emissions from a compression ignition engine with pure diesel fuel (D100), biodiesel mixed (B30), and clove oil 3000PPM was carried out. From the analysis, it was found that 5.27% reduction of particulate matter in biodiesel blended fuel andfurther when added clove in biodiesel blended fuel, 11.61% reduction of particulate matter was observed as compared to pure diesel because of a higher oxygen ratio contain in clove oil. The engine was run for 100 hours on each fuel sample (containing D100, B30, and B30+ clove oil) and the data was taken and tested per 25 hours for elemental analysis. The results manifest that metal concentration found different elements in lubricant oil i.e. lead (51.84), (24.89%), (23.255%) , copper (47.41%), (28.71%), (23.86%), nickel(37.88%), (32.32), (29.78%) and cadmium (46.12), (29.87%), (24.01%)in diesel, biodiesel blended fuel and biodiesel blended with clove oil respectively. This study found better results for engine life, which shows the lower metal concentration in biodiesel blended fuel and clove oil than diesel. Furthermore, the fuels investigated in this research can reduce the wear of engine parts because biodiesel and clove oil contains a high oxygen ratio. Moreover, it has been found that biodiesel and clove oil as an antioxidant, which is a positive impact on noise emission levels for compression ignition engine.